Brand Image of Ngilo-ilo Slahung Ponorogo Village as a Village of Reyog Hardware Craftsmen - Megantari, Krisna; Purwati, Eli; Anggoro, Ayub Dwi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This research is research that studies Public Relations (PR) in communication science. Brand Image is part of PR science which contains the steps and methods for creating branding, of course adapted to the object. The object this time is Ngilo-Ilo Village which is located in Slahung sub-district, Ponorogo Regency. Using the Branding Image Theory proposed by Satori and Komariah which states the stages by means of SWOT analysis and also mapping village potential. The results obtained are that Ngilo-Ilo Village has carried out SWOT efforts and village mapping has also been carried out, but there are still obstacles. Some of the obstacles were found in terms of natural resources, irrigation conditions which were still quite difficult and also weaknesses, namely related to the village Reyog event, which was felt to be lacking. The solution is to create deep infiltration wells which are useful for irrigating rice fields and also for the clean water needs of local residents. Then, regarding village Reyog events which are felt to be lacking, the suggestion is to be more active in carrying out more village event activities by collaborating with local Reyog artists to develop Reyog art even more optimally by prioritizing Reyog crafts from Ngilo-Ilo village